Resource Allocation Optimization and Academic Performance of Mathematics Students in Philippine State Universities: A Narrative Literature Review - Avila, Julmar; Gomez, Rico Jan; Tartar, Gelbert Sman (JPAIR Institutional Research, 2026)
Resource Allocation Optimization (RAO) is increasingly recognized as a structural determinant of academic performance in public higher education institutions, particularly within Philippine State Universities and Colleges (SUCs). This narrative literature review synthesizes theoretical and empirical studies examining the relationship between RAO - conceptualized through timeliness, adequacy, and accessibility of instructional resources - and the academic performance of Mathematics students. Drawing from education, educational psychology, and higher education management literature, the review identifies consistent causal pathways linking optimized resource allocation to instructional flow, academic self-efficacy, and competency development. Evidence further reveals a persistent discrepancy between satisfactory course grades and weaker performance in competency-based assessments, suggesting that systemic inefficiencies in instructional support constrain higher-order learning. By integrating administrative and pedagogical perspectives, this review positions RAO as a critical institutional predictor of Mathematics achievement and highlights the need for institution-specific empirical research to inform data-driven reforms in regional Philippine SUCs.
Keywords: Resource allocation optimization; Mathematics achievement; Academic performance; Philippine State Universities; Instructional resources